Quantification of water in hydrous ringwoodite - Thomas, Sylvia-Monique; Jacobsen, Steven D.; Bina, Craig R.; Reichart, Patrick; Moser, Marcus; Hauri, Erik H.; Koch-Müller, Monika; Smyth, Joseph R.; Dollinger, Günther (Frontiers in Earth Science, 2015)
Ringwoodite, γ-(Mg,Fe)2SiO4, in the lower 150 km of Earth’s mantle transition zone (410-660 km depth) can incorporate up to 1.5-2 wt% H2O as hydroxyl defects. We present a mineral-specific IR calibration for the absolute water content in hydrous ringwoodite by combining results from Raman spectroscopy, secondary ion mass spectrometery (SIMS) and proton-proton (pp)-scattering on a suite of synthetic Mg- and Fe-bearing hydrous ringwoodites. H2O concentrations in the crystals studied here range from 0.46 to 1.7 wt% H2O (absolute methods), with the maximum H2O in the same sample giving 2.5 wt% by SIMS calibration. Anchoring our spectroscopic results to absolute H-atom concentrations from pp-scattering measurements, we report frequency-dependent integrated IR-absorption coefficients for water in ringwoodite ranging from 78180 to 158880 L mol-1cm-2, depending upon frequency of the OH absorption. We further report a linear wavenumber IR calibration for H2O quantification in hydrous ringwoodite across the Mg2SiO4-Fe2SiO4 solid solution, which will lead to more accurate estimations of the water content in both laboratory-grown and naturally occurring ringwoodites. Re-evaluation of the IR spectrum for a natural hydrous ringwoodite inclusion in diamond from the study of Pearson et al. (2014) indicates the crystal contains 1.43 ± 0.27 wt% H2O, thus confirming near-maximum amounts of H2O for this sample from the transition zone.